Manifestasi Tuhan Dalam Tiga Agama: Islam, Hindu Dan Kristen - Fatkhurrohman, Abdul Azis (AL-ADYAN, 2024)
This article is intended to explore the concept of God's manifestation in three different religions. The agreement of each religion/belief on the Godhead, has become a guide for each of its adherents. On the other hand, the differences of other derivative concepts become very open to be studied in the comparative area. The Oneness of God, which is explained and agreed upon by all religions, lowers the conception and assertiveness shown by His own Essence to be understood upon His existence through His manifestation. It is in this area of manifestation that there is a distinction from each belief to "describe" God based on their respective religious texts. Based on this, this research will place three religions; Islam, Hinduism and Christianity in the area of the concept of manifestation understood by each of these religions. As a result, the three religions that are the object of this research have a narrative that is fully agreed upon in the concept of God's transcendence. This is based on the understanding that everything that becomes empirical reality is a necessity that causes everything. On the other hand, the transcendence of God also gave birth to a concept that leads to the rationality of existence to be proven. In this case, the concept of manifestation was born as one of the reflections in various religions in the world. Both Islam, Hinduism and Christianity have their own concepts in interpreting this. Islam and Hinduism are more similar in this regard, both having the concept of the manifestation of a transcendent God. Christianity, on the other hand, believes in a concept that is both transcendent and immanent at the same time.